2020
DOI: 10.1111/jfb.14552
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the post‐smolt growth pattern of wild one sea‐winter salmon (Salmo salarL.), and its linkage to surface warming in the eastern North Atlantic Ocean

Abstract: Variation in circulus spacing on the scales of wild Atlantic salmon is indicative of changes in body length growth rate. We analyzed scale circulus spacing during the post‐smolt growth period for adult one sea‐winter salmon (n = 1947) returning to Scotland over the period 1993–2011. The growth pattern of the scales was subjectively and visually categorized according to the occurrence and zonal sequence of three intercirculus spacing criteria (“Slow”, “Fast” and “Check” zones). We applied hierarchical time‐seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
(69 reference statements)
2
22
1
Order By: Relevance
“…Long‐term studies by Todd et al ( 2020 ) and Jonsson et al ( 2016 ) also observed a negative effect of SST on marine growth in Atlantic salmon populations. It has been postulated that increasing SST causes an indirect negative effect on growth through climate changes influencing prey availability (Jonsson et al, 2016 ; Todd et al, 2008 , 2020 ). In the present study, marine growth fell to an all‐time low for the smolt year classes around 2007, just as zooplankton abundance dropped sharply from a high level at about 10–15 g/m 2 down to about half the biomass (Figure 3A ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Long‐term studies by Todd et al ( 2020 ) and Jonsson et al ( 2016 ) also observed a negative effect of SST on marine growth in Atlantic salmon populations. It has been postulated that increasing SST causes an indirect negative effect on growth through climate changes influencing prey availability (Jonsson et al, 2016 ; Todd et al, 2008 , 2020 ). In the present study, marine growth fell to an all‐time low for the smolt year classes around 2007, just as zooplankton abundance dropped sharply from a high level at about 10–15 g/m 2 down to about half the biomass (Figure 3A ).…”
Section: Discussionmentioning
confidence: 86%
“…Earlier studies have also found conflicting influences of SST on marine growth (Bacon et al, 2009 ; Jensen et al, 2011 ; Todd et al, 2020 ), highlighting the fact that conclusions concerning drivers of marine growth rates of Atlantic salmon may differ among studies covering different regions and time periods. Long‐term studies by Todd et al ( 2020 ) and Jonsson et al ( 2016 ) also observed a negative effect of SST on marine growth in Atlantic salmon populations. It has been postulated that increasing SST causes an indirect negative effect on growth through climate changes influencing prey availability (Jonsson et al, 2016 ; Todd et al, 2008 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A sudden reduction in body growth was also observed among Atlantic mackerel following this reduction in plankton. A reduced growth of Atlantic salmon around 2005 has also been observed in France and Scotland ( 8 , 21 ), suggesting that the factors affecting southern Norwegian populations affected salmon populations across a large geographic area. We hypothesize that the oceanographic change in Arctic water caused a synchronous regime shift among trophic levels across a large area of the Northeastern Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 95%
“…Atlantic salmon ( Salmo salar ) migrate from rivers around the North Atlantic Ocean and spend at least one year in the ocean, where they feed before returning to their natal rivers ( 7 ). Upon return, a proportion of the salmon is captured by anglers, who report size of each fish and often provide researchers with a scale sample ( 8 ). Experienced scale readers can reconstruct individual growth in length at different periods at sea by analyzing growth pattern in the scales ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation